2021
DOI: 10.3389/fncel.2021.755875
|View full text |Cite
|
Sign up to set email alerts
|

The Causes and Long-Term Consequences of Viral Encephalitis

Abstract: Reports regarding brain inflammation, known as encephalitis, have shown an increasing frequency during the past years. Encephalitis is a relevant concern to public health due to its high morbidity and mortality. Infectious or autoimmune diseases are the most common cause of encephalitis. The clinical symptoms of this pathology can vary depending on the brain zone affected, with mild ones such as fever, headache, confusion, and stiff neck, or severe ones, such as seizures, weakness, hallucinations, and coma, am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 261 publications
0
26
0
Order By: Relevance
“…Regarding hRSV and SARS-CoV-2, learning and memory impairment cause cognitive problems that have been previously described [ 149 ]. In this line, it could be suggested that, as previously mentioned in the case of the influenza virus [ 142 , 154 ], the learning and memory impairment could be associated with an alteration in the levels of BDNF. Interestingly, after the infection with SARS-CoV-2, the patients that developed symptoms such as depression and anxiety presented lower levels of BDNF compared to the controls [ 160 ].…”
Section: Effect Of Cns Viral Infections On Neurotrophin Signalingmentioning
confidence: 78%
See 3 more Smart Citations
“…Regarding hRSV and SARS-CoV-2, learning and memory impairment cause cognitive problems that have been previously described [ 149 ]. In this line, it could be suggested that, as previously mentioned in the case of the influenza virus [ 142 , 154 ], the learning and memory impairment could be associated with an alteration in the levels of BDNF. Interestingly, after the infection with SARS-CoV-2, the patients that developed symptoms such as depression and anxiety presented lower levels of BDNF compared to the controls [ 160 ].…”
Section: Effect Of Cns Viral Infections On Neurotrophin Signalingmentioning
confidence: 78%
“…Neurotropic viruses can interfere with the correct signaling pathway of NTs and cause neurological pathologies. However, these pathologies can persist in the long term, causing disorders such as learning and memory impairment, mood and speech disorders, and degenerative diseases [ 154 ].…”
Section: Effect Of Cns Viral Infections On Neurotrophin Signalingmentioning
confidence: 99%
See 2 more Smart Citations
“…We have been fighting influenza for decades. Influenza induces short- and long-term symptoms and kills people in a similar way to COVID, and the same target population is at risk [ 75 , 76 , 77 , 78 , 79 , 80 , 81 ]. We have a standard of care in place with influenza symptoms and other respiratory diseases, some of which could have been better used to treat COVID.…”
Section: Alternative Measures To Vaccines To Fight the Pandemicmentioning
confidence: 99%